The Relationship Between Hyperglycemia and the Rheumatoid Factor in the Serum of Diabetic Patients (Baghdad Science Journal, 2009)
This study was conducted to determine the relationship between two most common diseases in Iraqis patients , which are Diabetic mellitus (DM) and Rheumatoid Arthritis (RA); seeking rheumatoid factor in hyperglycemic sera. The results revealed that ; 62.5% of hyperglycemic (HG) patients had positive rheumatoid factor (RF) . No difference in number between both gender of HG patients (20 males and 20 females ) , RF reaction was nearly similar in males and females of HG patients ( 12 &13 respectively ) . Only 40% out of patient controls had positive RF . None of the apparently healthy subjects had positive RF .